Effect of Tutorial Teaching Method for Knowledge and Skill of CPR - Tony Suharsono (University of Muhammadiyah Malang, 2016)
It is necessary nowadays to increase the importance and the skill of CPR in general public. One way is to introduce CPR training using traditional teaching method, tutorial. The aim of this experiment was to identify the increased knowledge and skill of CPR using 3 hours tutorial teacing method. This experiment was a quasy-experimental with pretest-posttest without control group design using 48 high school students as the samples, which were obtained using purposive sampling technique. Data from a pretest and a posttest were collected to measure the difference in knowledge and skill before and after the training. Results showed that the mean of knowledge was 6.94 (1.8) before training and 9.13 (1.2) after training, with p value 0.001. The respondents could not perform the complete procedure of the CPR. After training, the respondents showed the average results of 35.7 mm chest compression depth, 117.6 chest compression speed, 0.3 times ventilation, and 142.8 second of 5 CPR cycles duration. The respondents were unable to perform chest compression adequately for both depth and ventilation to the victim of cardiac arrest. It is suggested that CPR training is necessary for general public and that is should focus more on chest.